Managerial problems of remote work in Russian organisations: a remote workers’ perspective - V. Yu. Pronin (Вестник университета)
Remote work becomes an increasingly important way of organising labor, but its implementation requires significant changes both at the employees level and at the organisation level. Identification and response to key challenges organisations face when implementing remote work is now especially relevant given the significant expansion of remote working practices over the past two years. The article presents the findings from a sociological online survey conducted among Russian remote workers from various industries (N=402). The study shows that, in comparison with traditional models, remote work is estimated, in general, more positively, and is characterised by improvements in a number of characteristics important for management. The most problematic areas include: organisational and technical support for remote work, and problems related to social roles and social protection. The main factor contributing to the reduction of the severity of most problems is the accumulation of experience in working remotely. This indicates successful adaptation to the remote format both on the part of employees and on the part of the organisation.